Analisis Makna Dalam Lirik Lagu Masa Mudaku Habis Karya Ghea Indrawari: Kajian Semiotika Rholand Barthes - Kartika, Yunda; Edria, Ade Lola; Ibrahim, Dimas; Ningsih, Mutiara Umami; Pranata, Jaya Reza (Peneliti.net, 2024)
Abstract Received: Revised: Accepted: This research discusses the meaning of denotation, connotation and myth in the lyrics of the song